A DEEP DIVE IN TO CARBON TECHNOLOGY DEVELOPMENT - Desilwa, Pro.Robin Desilwa (International Journal of Multidisciplinary Research and Studies, 2021)
China must follow an occasional carbon pathway, within which technology plays a key role in the future economy and social development. The results show that there are lots of potential and opportunities for China to maneuver towards a coffee-carbon society when given enhanced and accelerated applications and expansions of key low-carbon technologies. Strong policy and measure support from all sectors in China are needed to attain this goal